An empirical study on the usage behavior of mobile health management service systems for flight attendants in the digital Age - Liu, Yuting; Li, Haiyan (Frontiers in Digital Health, 2025)
ObjectiveMobile health management service systems have rapidly emerged in today's digital age, providing a new way to manage personal health with great potential value. This study deeply explores the use behavior and influencing factors of mobile health management service systems for flight attendants in the context of the "Digital age".MethodsThe study mainly adopted the questionnaire survey method, used SPSS24.0 and AMOS24.0 software for data analysis, and used statistical methods such as factor analysis, regression analysis, and path analysis to verify the effectiveness of the model and explore the relationship between key variables.Results(1) The usage rate of the health management service system among flight attendants is not as high as expected, but the use rate of sports health monitoring applications reached 66.5%, and the daily frequency of use was as high as 25.52%, (2) Perceived ease of use and perceived usefulness have a positive and significant impact on intention to use, (3) Privacy concerns have a positive impact on intention to use Significant negative impact.ConclusionThe study points out that ease of use and usefulness are key factors in attracting flight attendants to use mobile health management service systems. System designers need to pay attention to this aspect. Flight attendants have a strong sense of privacy protection, and the system must provide a strong privacy protection mechanism to win trust. Therefore, system developers should strive to provide practical value, such as health advice and data tracking, to stimulate user enthusiasm. In addition, this article has certain limitations in the study of sample selection and the discussion of mediating relationships. Future research can be further improved in this regard.